Penentuan Penerimaan Beasiswa Menggunakan Metode Modified K-Nearest Neighbor - Caesaredi Rama Raharya; Nurul Hidayat; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In determining the acceptance of students scholarship, the officers often face problem selecting student who are eligible for a scholarship that caused by several factors such as the number of students who apply for a scholarship while the quota for students who get scholarships is relatively small, the number of parameters used as a reference in determining the students who are eligible for a scholarship and the officers who are given only a relatively short time in determining the awardee. Therefore implement a classification system is required to this issue for help facilitate the scholarship selection officer. This research was using Modified K-Nearest Neighbor method. Modified Method K-Nearest Neighbor is modified method from K-Nearest Neighbor consists of the process of calculating distance euclidean, calculation of validity value and weight voting calculation. The highest average accuracy results obtained based on the tests and normalization data that have been done is 87.2%.